Dinamika Perilaku Gen Z Sebagai Generasi Internet - Cindy Nurlaila; Qurrotul Aini; Sharla Setyawati; April Laksana (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Gen Z or generation Z is often called the big "internet generation" with technology, digital platforms, and unlimited access to internet information making gen Z familiar with internet advances. this research studies the behavior of gen Z as an internet generation in life in various aspects, gen Z has multitasking skills, gen Z challenges in the corporate world, gen Z interaction in the digital world, the influence of social media on self-identity, using a qualitative approach. Social media plays a very important role in shaping self-identity, high attachment to the internet has a risk of dependence and mental health disorders. The results of this study are expected to show the behavioral dynamics of gen Z which are different from previous generations so that it requires a separate communication approach to be able to understand gen Z as the internet generation.